Plasmodium malariae Prevalence and csp Gene Diversity, Kenya, 2014 and 2015 - Eugenia Lo; Kristie Nguyen; Jennifer Nguyen; Elizabeth Hemming-Schroeder; Jiaobao Xu; Harrisone Etemesi; Andrew Githeko; Guiyun Yan (Emerging Infectious Diseases, 2017)
In Africa, control programs that target primarily Plasmodium falciparum are inadequate for eliminating malaria. To learn more about prevalence and genetic variability of P. malariae in Africa, we examined blood samples from 663 asymptomatic and 245 symptomatic persons from western Kenya during June–August of 2014 and 2015. P. malariae accounted for 5.3% (35/663) of asymptomatic infections and 3.3% (8/245) of clinical cases. Among asymptomatic persons, 71% (32/45) of P. malariae infections detected by PCR were undetected by microscopy. The low sensitivity of microscopy probably results from the significantly lower parasitemia of P. malariae. Analyses of P. malariae circumsporozoite protein gene sequences revealed high genetic diversity among P. malariae in Africa, but no clear differentiation among geographic populations was observed. Our findings suggest that P. malariae should be included in the malaria elimination strategy in Africa and highlight the need for sensitive and field-applicable methods to identify P. malariae in malaria-endemic areas.